The effectiveness of means of escape for disabled people in high rise residential building / Mirdeeliana Amir - Amir, Mirdeeliana (2008)
In 1995, government has state that every high rise building should be provided with means of escape for disabled people, after that, Malaysian Standard 1184:2002 Code of Practice On Access for Disabled Persons to Public Buildings is published. This guideline has amendment the Uniform Building By Law (UBBL) 1984, clause "building design requirement" for disabled people which state that every new building should providing with access for disabled person, including providing ramps and railings, special pavement for wheelchair user, evacuation lift, parking area, toilet and etc. The objective of the research is to study the effectiveness of means of escape at high rise residential building. This study is carried out on the following three objectives which includes; to study the relevant guidelines about the design of means of escape for disabled people in high-rise residential building; to analysis the design of means of escape for disabled people in high rise residential building at Kuala Lumpur and Selangor; to examine whether the high-rise residential building meet the requirement with reference to Building Regulation; to suggest a positive recommendation to improve the means of escape during in a fire evacuation. A total forty-three (43) questionnaires were distributes to the case study buildings. From the analysis it was found that majority high rise residential building is not providing with this access. The case studies only focus on building with means of escape for disabled person only. It can be concluded that, based on the case studies, the facilities of means of escape that provided for disabled people in this high rise residential building is effective.